O direito produto da notícia: a morte estampada nos jornais - Luana Magalhaes de Araujo Cunha (2014)
The present work investigates how criminal law is transformed into a product to be consumed by many readers/clients of daily newspapers. We start from the assumption that in a society that depends on the means of mass communication to grasp reality, journalism is the means by which information gain visibility and legitimacy, which is extremely important for the formation of public opinion and the internalization of concepts and worldviews by individuals, including in what regards Law. The journalistic speech object of this research, extracted from newspaper articles reporting homicides with criminal intent, proved to be rich in discursive constructions that meet basic social functions: establishment of paradigms, stigmas, ways of acting and thinking that operate symbolically in individuals in a way that promotes an exemplary, direct and immediate public sanction.